Long-term patient-reported outcomes and patient-reported outcome measures after injury: the National Trauma Research Action Plan (NTRAP) scoping review. Issue 5 (May 2021) - Herrera-Escobar, Juan P.; Osman, Samia Y.; Das, Sophiya; Toppo, Alexander; Orlas, Claudia P.; Castillo-Angeles, Manuel; Rosario, Angel; Janjua, Mahin B.; Arain, Muhammad Abdullah; Reidy, Emma; Jarman, Molly P.; Nehra, Deepika; et al.
Abstract : BACKGROUND: The aim of this scoping review is to identify and summarize patient-reported outcome measures (PROMs) that are being used to track long-term patient-reported outcomes (PROs) after injury and can potentially be included in trauma registries. METHODS: Online databases were used to identify studies published between 2013 and 2019, from which we selected 747 articles that involved survivors of acute physical traumatic injury aged 18 years or older at time of injury and used PROMs to evaluate recovery between 6 months and 10 years postinjury. Data were extracted and summarized using descriptive statistics and a narrative synthesis of the results. RESULTS: Most studies were observational, with relatively small sample sizes, and predominantly on traumatic brain injury or orthopedic patients. The number of PROs assessed per study varied from one to 12, for a total of 2052 PROs extracted, yielding 74 unique constructs (physical health, 25 [34%]; mental health, 27 [37%]; social health, 12 [16%]; cognitive health, 7 [10%]; and quality of life, 3 [4%]). These 74 constructs were assessed using 355 different PROMs. Mental health was the most frequently examined outcome domain followed by physical health. Health-related quality of life, which appeared in more than half of the studies (n = 401), was the most common PRO evaluated, followed by depressive symptoms. Physical health was the domain with the highest number of PROMs used (n = 157), and lower-extremity functionality was the PRO that contributed most PROMs (n = 33). CONCLUSION: We identified a wide variety of PROMs available to track long-term PROs after injury in five different health domains: physical, mental, social, cognitive, and quality of life. However, efforts to fully understand the health outcomes of trauma patients remain inconsistent and insufficient. Defining PROs that should be prioritized and standardizing the PROMs to measure them will facilitate the incorporation of long-term outcomes in national registries to improve research and quality of care. LEVEL OF EVIDENCE: Systematic Reviews & Meta-analyses, Level IV Abstract : Supplemental digital content is available in the text.